TOXICITY OF THE HERBICIDE 2, 4-D DIMETHYL AMINE SALT ON BEHAVIORAL, HISTOLOGICAL AND OXIDATIVE STRESS BIOMARKERS OF AFRICAN CATFISH CLARIAS GARIEPINUS (BURCHELL, 1822) FINGERLINGS - Hamisu, Y.; Auta, J.; Bawa, Bolanle S. (FUDMA Journal of Sciences, 2024)
The aim of this paper was to assess the toxicological impacts of the Herbicide 2, 4-D Dimethyl amine salt on Clarias gariepinus fingerlings. The fishes were exposed to lethal concentration of 0.00, 1.34, 1.42, 1.48, 1.54 and 1.60ml/L for 96 hours as well as sub-lethal concentrations of 0.00, 0.069, 0.138 and 0.276ml/l of 2, 4-D Dimethyl amine salt for 8 weeks. The value of 96 hours LC50 was 1.385ml/L.  Respiratory disturbance, loss of equilibrium, and sudden fish death were observed in 96hrs of exposed fish, and these varied greatly with increase in concentration of the toxicant, with a trend of significant (p
Keywords: 2, 4-D Dimethyl Amine Salt; Behaviour; Herbicide; Histology; Oxidative stress biomarkers; Toxicity